KECENDERUNGAN WACANA BERITA JURNALISME WARGA DI LIPUTAN6.COM:KASUS KORUPSI DANA BANSOS COVID-19 MENSOS JULIARI BATUBARA - Nurfadhilah Bahar; Rahmawati Latief (Fakultas Dakwah dan Komunikasi, 2021)
This research examines the tendency of citizen journalism news discourse through Liputan6.com website. The cornerstone of this study is the analysis of critical discourse with the Teun A. Van Dijk approach model. This research aims to see the tendency of citizen journalism news discourse entitled “Mensos Juliari Batubara Tersangka Korupsi Bansos COVID-19, Warganet Tagih Janji Hukum Mati ke KPK